Bridging Intelligence and Agility: The Strategic Role of Dynamic Managerial Capability in SMEs - Ida Ketut Kusumawijaya; Partiwi Dwi Astuti; Wartana I Made Hedy; Adi I Ketut Yudana (PT ARRUS Intelektual Indonesia, 2026)
Organizational intelligence, dynamic managerial capability, and organizational agility are increasingly critical for small and medium-sized enterprises facing volatile and highly competitive environments, where survival depends on the ability to recognize change and respond with speed and precision. This study investigates how organizational intelligence affects organizational agility, both directly and indirectly through dynamic managerial capability, among SMEs in Bali. Using a quantitative explanatory approach, data were collected from 153 SME managers through an online questionnaire and analyzed using partial least squares structural equation modeling. The findings reveal that organizational intelligence exerts a strong positive effect on dynamic managerial capability and organizational agility, while dynamic managerial capability also strongly enhances organizational agility. Moreover, dynamic managerial capability partially mediates the relationship between organizational intelligence and organizational agility, showing that intelligence becomes more strategically valuable when converted into managerial sensing, interpretation, and resource reconfiguration. The study’s novelty lies in positioning organizational intelligence not merely as an informational asset, but as an upstream strategic capability whose influence on agility is transmitted through managerial capability. These results imply that SME agility can be strengthened by simultaneously improving intelligence systems and managerial capability development.